Changing climate sensitivity of secondary growth following extreme drought events in forest ecosystems: a global analysis - Christopher Leifsson; Allan Buras; Anja Rammig; Christian Zang (Environmental Research Letters, 2023)
Understanding tree-response to extreme drought events is imperative for maintaining forest ecosystem services under climate change. While tree-ring derived secondary growth measurements are often used to estimate direct and lagging drought impacts, so-called drought legacies, underlying physiological responses remain difficult to constrain across species and site conditions. As extreme droughts may alter the functioning of plants in terms of resource allocation being shifted towards repair and physiological adjustments, climate control on growth may consequently be altered until physiological recovery is completed. In this context, we here advance the concept of drought legacy effects by quantifying ‘functional legacies’ as climate sensitivity deviations (CSD) of secondary growth after droughts, i.e. temporary alterations of climate-growth relations. We quantified climate sensitivity deviations after extreme drought events by applying linear mixed-effects models to a global-scale, multi-species tree-ring dataset and differentiated responses by clades, site aridity and hydraulic safety margins (HSMs). We found that while direct secondary growth legacies were common across these groups, responses in post-drought climate sensitivity deviations were nuanced. Gymnosperms showed weaker coupling between secondary growth and the dominant climatic driver after droughts, a response that was narrowed down to gymnosperms with a small HSM, i.e. risky hydraulic strategy. In comparison, angiosperms instead showed stronger coupling between secondary growth and the dominant climatic driver following droughts, which was narrowed down to the angiosperms growing in arid sites. These results are consistent with current understanding of physiological impairment and carbon reallocation mechanisms, and the distinct functional responses suggest functional legacies quantified by climate sensitivity deviations is a promising avenue for detecting and thus studying physiological mechanisms underlying drought-responses in tree growth on large scales.